Proteome comparison of helicobacter pylori isolates associated with four disease groups - McWilliams, Tracy (Curtin University, 2006)
The Gram-negative bacterium Helicobacter pylori is found in human gastric mucosa. H. pylori, one of the most common chronic bacterial infections of humans, is present in almost half of the world population. It is associated with chronic gastritis, non-ulcer dyspepsia, gastric and duodenal ulcers, and malignant neoplasms. The aim of this study was to detect microbial candidate protein markers whose presence might be correlated with the development of four different clinical consequences of H. pylori infection, gastric ulceration [GU], duodenal ulceration [DU], non-ulcer dyspepsia [NUD] and gastritis [GI]. Eleven H. pylori isolates associated with these outcomes were analysed. The total complement of protein from these H. pylori isolates were resolved by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and compared using PDQUEST pattern analysis software. Relationships between the isolates associated with specific disease outcomes were determined by cluster analysis.Fifty six disease specific proteins were then characterised by tryptic peptide-mass fingerprinting using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Up to 1165 protein species were resolved from each H. pylori strain. Proteome analysis revealed that only 470 (40%) of the proteins detected were common to all eleven isolates. Twenty six of the 56 disease specific proteins that were selected for identification consisted of spots whose expression is altered in response to stress conditions or those that can affect H. pylori cell division and the cell membrane. The remaining 30 proteins had no known function. This study has provided further confirmation of the extensive variation that the bacterium H. pylori exhibits at the proteome level. Most significantly this study has found, through the application of cluster analysis and protein matching, that isolates do form disease groups. Comparative proteome analysis is a useful method for highlighting the extensive strain variation that H. pylori exhibits and to determine if any disease specific proteins exist.